GAMBARAN LINGKUNGAN DAN VEKTOR DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS TEMANGGUNG TAHUN 2017 - Cahyati, Widya Hary; Sanjani, Jauharotusf Syifa Kusrah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Cases of DHF in Temanggung District had increased from 2014 - 2016 and the DHF insidence rate was in the top three of the highest level in Central Java. The aim of this research is to describe the environmental and vector of Dengue Hemorrhagic Fever in DHF Case in Temanggung Primary Health Center Working Area.This is a descriptive research with an observational analytic approach. Samples of this research are 48 DHF cases with simple random sampling, while the mosquito samples were taken by spot surveytechniques. The instruments which used in this research are measurement and observation sheets, and questionnaire sheets. The data analysis is shown in the form of frequency table.The result showed that the average of physical environment consist of temperatures around 24.3-27.2oC, 73-94% of humidity, and 0-67mm of rainfall. The most type of water reservoirs was bathtubs, and it is located mostly in the house. The biological environment showed that there are 38 houses with the match criteria of trees (shady trees with at least 5 meters of height and full of leaves yet ≤ 100 meters away from sample’s house), additionally there is no bush with the match criteria (a clump of trees with the maximum height of 2 meters, ≥ 2 meters wide, yet ≤ 100 meters away from sample’s house). The social environment showed that the category of DHF knowledge was mostly in the moderate category, the category of action respondents also showed that they mostly not supporting the prevention of DHF, and the density of occupancy was not dense. The most dominantis of mosquito was Aedes aegypti. This research’s recommendation is to conduct the integrated vector control which involve all components in Temanggung Primary Health Center Working Area.